Closer-to-nature forest management approaches in Finland - Korhonen, Kari T.; Huuskonen, Saija; Kolström, Taneli; Kurttila, Mikko; Punttila, Pekka; Siitonen, Juha; Syrjänen, Kimmo (Natural Resources Institute Finland (Luke), 2021)
The European Commission Biodiversity Strategy for 2030 proposes to continue and further develop biodiversity-friendly practices, such as closer-to-nature-forestry, to achieve the ambitious biodiversity targets. In Finland, forestry land covers 86% of the land area and thus the protection of biodiversity is closely connected to forest management. In this report we review the elements in Finnish forest legislation, PEFC-forest certification scheme and forest management guidelines that are related to and support closer-to-nature forest management practices. We include a brief description of the specific features of boreal forest ecosystems, forest resources of Finland as well as a brief description of the forest management practices and governance.
Keywords: forest management; biodiversity